Use of Molecular Profiling to Guide Treatment Decisions in Patients with Neuroendocrine Tumors: Preliminary Results. Issue 4 (April 2016) - Cutler, Holt S.; Ogando, Paul; Uhr, Joshua H.; Gonzalez, Dani O.; Warner, Richard R.P.; Divino, Celia M.
This case series demonstrates the potential of molecular profiling to improve selection of anti-tumor therapies in the treatment of patients with neuroendocrine and carcinoid tumors. Carcinoid tumors resected at one institution over a 3-year period were sent for molecular profiling to guide choice of treatment. Potentially beneficial therapies were identified based on the measured expression of 20 proteins and oncogenes and a comprehensive review of the chemotherapy response literature. The clinical charts of 41 patients were reviewed retrospectively, and 12 were selected as representatives of the range of effects molecular profiling has on carcinoid treatment. Their presentation, molecular profile results, treatment, and disease progression is reviewed in the following case series. A total of nine patients were treated with drugs identified as potentially beneficial by molecular profile reports. These include capecitabine, 5-fluorouracil, temozolomide, oxaliplatin, and gemcitabine. Based on clinical symptoms, serum markers of disease, and radio-graphic evidence five of nine patients responded to treatment, two had mixed responses, and two did not respond to treatment. At this early juncture, our critique of molecular profiling for neuroendocrine tumors is favorable, as a significant number of our patients responded to drugs identified by molecular profiling as potentially beneficial.